2021
DOI: 10.14444/8038
|View full text |Cite
|
Sign up to set email alerts
|

Dural Tears During Lumbar Spinal Endoscopy: Surgeon Skill, Training, Incidence, Risk Factors, and Management

Abstract: Background: Incidental dural tears during lumbar endoscopy can be challenging to manage. There is limited literature on their appropriate management, risk factors, and the clinical consequences of this typically uncommon complication.Materials and Methods: To improve the statistical power of studying durotomy with lumbar endoscopy, we performed a retrospective survey study among endoscopic spine surgeons by email and chat groups on social media networks, including WhatsApp and WeChat. Descriptive and correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Moreover, rates of recurrent disc herniation and dural tear did not significantly differ between both groups. The rates of dural tear following both techniques were relatively low (less than 3%), in accordance with a survey study by Lewandrowski et al, 34 but they reported a higher risk of dural tear in IELD than TELD due to the use of power tools or sharp instruments during ligamentum flavum resection and the fragile posterior dural sac exposure. However, we believe that surgeons’ learning curve significantly affected the complication rates.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, rates of recurrent disc herniation and dural tear did not significantly differ between both groups. The rates of dural tear following both techniques were relatively low (less than 3%), in accordance with a survey study by Lewandrowski et al, 34 but they reported a higher risk of dural tear in IELD than TELD due to the use of power tools or sharp instruments during ligamentum flavum resection and the fragile posterior dural sac exposure. However, we believe that surgeons’ learning curve significantly affected the complication rates.…”
Section: Discussionsupporting
confidence: 88%
“…Secondly, once durotomy occurs, alternative measures should be taken. Meaningful work has already been conducted to codify the workflow for dealing with durotomy [ 32 , 36 , 37 ]. Its management, mainly regarding whether the small size of the durotomy should be repaired or not, seems controversial.…”
Section: Discussionmentioning
confidence: 99%
“…With the surgical volume rising, publications on the incidence and management of complications of endoscopic lumbar decompression procedures have appeared in print, alerting spinal surgeons interested in implementing these innovative minimally invasive surgeries into their program to their potential pitfalls [ 12 , 19 , 22 , 23 , 24 ]. While complication rates are generally lower than with traditional translaminar surgeries [ 24 ], interlaminar and transforaminal endoscopic decompression surgeries are associated with their specific sets of difficulties and postoperative sequelae that could catch the novice surgeon unfamiliar with these pitfalls off guard.…”
Section: Introductionmentioning
confidence: 99%
“…While complication rates are generally lower than with traditional translaminar surgeries [ 24 ], interlaminar and transforaminal endoscopic decompression surgeries are associated with their specific sets of difficulties and postoperative sequelae that could catch the novice surgeon unfamiliar with these pitfalls off guard. One such example relates to small dural tears that can easily be encountered in the posterior dural sac during the interlaminar approach or in the axilla formed between the exiting and traversing nerve roots during the transforaminal approach [ 22 ]. The latter is referred to as the hidden zone of Macnab because durotomies in this difficult-to-access and difficult-to-visualize area are most common and by far less common in any other portion of the epidural space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation